In memoriam Thomas Friedrich (1949–2018). - Agricola, Ilka; Bögelein, Verena; Duzaar, Frank (Annals of Global Analysis and Geometry, 2019)
Thomas Friedrich, who founded the journal ‘Annals of Global Analysis and Geometry’ together with Rolf Sulanke in 1983 and acted as editor in chief for more than 3 decades, died in Marburg (Germany) on February 27, 2018, at the age of sixty-eight of COPD and lung cancer. Besides sketching Thomas’s biography and scientific work, it is our goal in this obituary to tell the founding story of ‘his’ journal. This will reflect his life and character, and will provide a remarkable insight into twentieth century science policies as well as the changes that scientific publishing has undergone in the past decade